Prospective payment for Medicare hospital capital: Implications of the research - Cotterill, Philip G. (CENTERS for MEDICARE & MEDICAID SERVICES, 1992)
The special characteristics of capital have an important effect on the cross-section variation in hospitals' capital costs. Variables reflecting capital age and financing differences perform as expected and add substantial explanatory power to capital cost models. However, even with the inclusion of these variables, the capital-cost models perform poorly compared with total-cost models. The empirical findings of this article support using the total-cost models to develop a common set of adjustment factors for capital and operating payment amounts in the Medicare prospective payment system.